Multi-objective optimization of single-phase flow heat transfer characteristics in corrugated tubes - Kirkar, Safak Metin; Gonul, Alisan; Celen, Ali; Dalkilic, Ahmet Selim (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2023)
In this study, the use of corrugated surfaces as one of the passive heat transfer improvement methods on straight tubes is numerically investigated related to the determination of Nusselt number, friction factor, and perfor-mance evaluation criteria. With the same diameter of 5.75 mm and length of 390 mm, 9 corrugated tubes having corrugation pitches of 6, 12 and 18 mm, and depths of 0.6, 0.8 and 1.0 mm are considered for the parametric studies. Water is employed as a operating fluid with Reynolds number values from 480 to 6100 covering different flow regimes. Sensitivity analyses by Genetic Aggregation Response Surface Methodology and multi-objective optimization analyses by NSGA-II are performed in order to maximize heat transfer and minimize pressure drops. It is determined that the thermal-flow augmentation created by the use of corrugated surfaces in laminar flow conditions is quite higher than those in the turbulent region of the smooth tube. According to the obtained optimum parameters and flow conditions, the maximum value of the performance evaluation criteria is 2.48 in comparison to the use of equivalent smooth and corrugated tubes. In addition, Nusselt number and friction factor equations are suggested by using 220 data points within deviation bands of +/- 10% and +/- 15%, respectively.
Keywords: Heat transfer enhancement; Corrugated tube; Computational fluid dynamics; Response surface methodology; Genetic algorithm; Optimization; PRESSURE-DROP CHARACTERISTICS; TRANSFER ENHANCEMENT; PERFORMANCE EVALUATION; RESPONSE-SURFACE; EQUATIONS; GEOMETRY; LAMINAR; MASS; Thermodynamics; Engineering